2022
DOI: 10.1016/j.autrev.2021.102927
|View full text |Cite
|
Sign up to set email alerts
|

Response to SARS-CoV-2 vaccination in immune mediated inflammatory diseases: Systematic review and meta-analysis

Abstract: Objectives The treatment for COVID-19 often utilizes immune-modulating drugs. These drugs are also used in immune mediated inflammatory diseases (IMIDs). We performed a systematic review about seroconversion after SARS-CoV-2 vaccination in patients with IMIDs and impact of various drugs on seroconversion rates. Methods Electronic databases were searched to identify relevant studies reporting seroconversion rates following SARS-CoV-2 vaccination in IMIDs. We calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
132
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 55 publications
(25 reference statements)
14
132
2
3
Order By: Relevance
“…In contrast, the available studies to date show that a full course of mRNA vaccine in patients with IMID elicit a response in 78-100% of subjects [21], showing reduced serum antibody IgG titers and serum neutralizing activity as compared to healthy controls [10,13,14,[22][23][24]. Reduced humoral and cellular immune response (CD8 +) to COVID-19 mRNA vaccines were found by Haberman et al in IMID treated with methotrexate and by Mahil et al in psoriasis (47% and 62% responders, respectively) [23,25], although this finding has not been confirmed in our and other studies (> 80% responders) [14,21,22,26]. Some factors such as the characteristics of enrolled populations and selection criteria may explain this difference.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, the available studies to date show that a full course of mRNA vaccine in patients with IMID elicit a response in 78-100% of subjects [21], showing reduced serum antibody IgG titers and serum neutralizing activity as compared to healthy controls [10,13,14,[22][23][24]. Reduced humoral and cellular immune response (CD8 +) to COVID-19 mRNA vaccines were found by Haberman et al in IMID treated with methotrexate and by Mahil et al in psoriasis (47% and 62% responders, respectively) [23,25], although this finding has not been confirmed in our and other studies (> 80% responders) [14,21,22,26]. Some factors such as the characteristics of enrolled populations and selection criteria may explain this difference.…”
Section: Discussionmentioning
confidence: 88%
“…Initial immunogenicity data available for at-risk subgroups showed a high proportion of non-responders and low antibody responses to the SARS-CoV-2 spike protein in patients who received solid-organ transplantation [18], patients treated for solid cancer [19], or in patients with ongoing hemodialysis [20]. In contrast, the available studies to date show that a full course of mRNA vaccine in patients with IMID elicit a response in 78-100% of subjects [21], showing reduced serum antibody IgG titers and serum neutralizing activity as compared to healthy controls [10,13,14,[22][23][24]. Reduced humoral and cellular immune response (CD8 +) to COVID-19 mRNA vaccines were found by Haberman et al in IMID treated with methotrexate and by Mahil et al in psoriasis (47% and 62% responders, respectively) [23,25], although this finding has not been confirmed in our and other studies (> 80% responders) [14,21,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Observational data in small cohorts of patients with rheumatoid arthritis have indicated that rituximab impairs serological SARS-CoV-2 vaccine responses. 8 , 9 , 10 , 11 Previous reports have suggested that T cells are necessary for protection against severe COVID-19 in settings of low antibody titres, 12 for rapid and efficient resolution of COVID-19 13 and for protection against fatal outcomes in patients treated with anti-CD20 therapies for haematological malignancies. 14 To date, sparse data exist regarding cellular responses to SARS-CoV-2 vaccines in rituximab-treated patients with rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, certain therapies (anti-TNF, anti-IL17, anti-IL6, anti-IL12/23) seem not to impact seroconversion rates while others (anti-CD20, anti-CTLA-4) result in poorer responses in patients treated with immunosupressors for different rheumatic and non-rheumatic diseases ( 2 , 5 ). Furthermore, we confirm a good response to vaccination in patients treated with TNF blockers, anti-IL 17, anti-IL6, anti-12/23 therapies and observed a poor response in patients treated with anti-CD20/anti-CTLA-4 although numbers are low (n=5).…”
mentioning
confidence: 99%
“…Furthermore, we confirm a good response to vaccination in patients treated with TNF blockers, anti-IL 17, anti-IL6, anti-12/23 therapies and observed a poor response in patients treated with anti-CD20/anti-CTLA-4 although numbers are low (n=5). Conflicting results were reported in patients using methotrexate ( 5 , 6 ). We did not found that methotrexate hampers humoral response to vaccine in our cohort.…”
mentioning
confidence: 99%